Persepsi Etis Aparat Pajak dan Mahasiswa: Studi Empiris pada Pemeriksa Pajak, Account Representative dan Mahasiswa Sekolah Tinggi Akuntansi Negara - Marsono Abdurrasyid; Eko Suwardi (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2010)
The objectives of this study were to empirically test the difference of ethical perceptions between tax officers and students, and to test the difference between groups in tax officers and students. Population of this study was tax officers in Java except West Java and Banten provinces and students of Sekolah Tinggi Akuntansi Negara (STAN). Questionnaires were distributed to 1000 tax officers and 400 students. The number of returned and qualified questionnaires was 830 consisting of 535 from tax officers and 295 from students. The difference test with .05 significant level indicated that there was significant difference in ethical perceptions between the tax officers and the students where the tax officers had better ethical perceptions than the students did. The other result revealed that there was no significant difference in ethical perceptions between the tax auditors and the account representatives with a tendency that account representative’s ethical perceptions were better than tax auditor’s. Besides, based on the result of the difference test between the freshmen and the seniors, there was no difference in ethical perceptions with a tendency that the senior’s ethical perceptions were better than the freshmen’s. The implication of this study includes a need to continuously enforce ethical values in tax institution through examples from their executives in maintaining good ethical climate and culture. Besides, to engraft ethical values to among students of STAN as tax officer candidates, appropriate ethical education formats are needed both when they sit in their college and when they are about to be tax officers.